2022
DOI: 10.1016/j.qref.2022.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Bank profitability and economic growth

Abstract: This paper analyses the effect of bank profitability on economic growth. While policymakers have shown major concerns for low levels of bank profitability, there are no empirical studies on the growth effects of bank profitability. To fill this gap, we investigate the impact of bank profitability on economic growth using a sample of 133 countries during the period 1999-2013 with several empirical approaches. Our first major conclusion is that a high current level of bank profitability contributes positively to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 54 publications
3
17
0
Order By: Relevance
“…The results of this study are in line with research (Antypas et al , 2020), (Hamza and Saadaoui, 2018) (Abasimel, 2022; Asteriou and Spanos, 2019; Bernard Azolibe, 2022; Bist, 2018; Boukhatem and Ben Moussa, 2018; Klein and Weill, 2022; Naz and Gulzar, 2022; Saleem et al , 2021; Sharma et al , 2018). Islamic banking is favorably associated with economic growth, even when other growth variables are taken into account.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The results of this study are in line with research (Antypas et al , 2020), (Hamza and Saadaoui, 2018) (Abasimel, 2022; Asteriou and Spanos, 2019; Bernard Azolibe, 2022; Bist, 2018; Boukhatem and Ben Moussa, 2018; Klein and Weill, 2022; Naz and Gulzar, 2022; Saleem et al , 2021; Sharma et al , 2018). Islamic banking is favorably associated with economic growth, even when other growth variables are taken into account.…”
Section: Resultssupporting
confidence: 90%
“…By affecting financial stability, bank profitability can have an impact on economic growth. Numerous studies have demonstrated the link between financial stability and economic growth (Klein and Weill, 2022). The impact of financial sector development on a country’s economic growth has been widely theorized by empirical literature (Asteriou and Spanos, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Rapid economic growth increases bank profitability. Therefore, bank profitability can support economic growth by enhancing financial stability (Demirgüç-Kunt and Huizinga 1999; Claeys and Schoors 2007;Klein and Weill 2022). However, the effect of the inflation rate on profitability depends on whether it can be anticipated or not.…”
Section: Findings Of the Sgmm Regressionmentioning
confidence: 99%
“…Abu-Alkheil et al (2018) found that liquidity risk affects the placing of some assets in a non-recoverable form, and reducing liquidity risk leads to lower profitability. Klein and Weill (2022) argued that banks' profitability is affected by their asset size, which promotes economies of scale, and larger banks have access to cheaper resources and more reliable funding (Vera-Gilces et al 2020). Table 2 shows the control parameters.…”
Section: Variable Definitionsmentioning
confidence: 99%